Emergence in the WAEMU and EMCCA areas - Ntwali, Valéry IRAGI; Centwali, Guillain CIRHUZA (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The Economic and Monetary Community of Central Africa (EMCCA) and the West African Economic and Monetary Union (WAEMU) have succeeded in stabilizing their monetary systems, but this monetary stability has not been accompanied by real emergence. The economies of most of the member states of these two organizations are based on commodities and cocoa, which means that they are completely volatile and therefore lack the stability necessary for real emergence. This study based mainly on documentary research through the exploitation of reports produced by various international and regional institutions such as the IMF, the World Bank, the African Development Bank, ECOWAS, etc., and the writings of various emergence theorists, shows the role that industrialization and diversification of the economies of the WAEMU and EMCCA zones should play in the development of the economies of the member states and the improvement of the living conditions of the populations.
Keywords: CEMAC; Emergence; Spaces; UEMOA; WAEMU

Four Essays on Tax Transition Reform in Developing Countries - Adandohoin, Kodjo (Université Clermont Auvergne, 2021)
Ces dernières années, la plupart des pays en développement sont confrontés à la nécessité de concilier deux impératifs : d’une part, une demande sociale forte qui nécessite un besoin de ressources publiques supplémentaires, et d’autre part le désarmement tarifaire consécutif aux politiques d’ouverture commerciale, qui les prive de la majeure partie de leurs recettes budgétaires. D’où l’impérieuse nécessité pour ces pays d’assurer une transition dans la structure de leur prélèvement public c’est à dire de transférer la pression fiscale du commerce extérieur vers la fiscalité domestique. Cette thèse s’intéresse à cette problématique et vise à étudier les conditions de réussite d’un tel phénomène dans les pays en développement au travers de quatre essais empiriques. Le premier essai concerne le rôle de la TVA et des droits d’accises dans une première vague de transition. La TVA étant un impôt neutre et à très large assiette fiscale, cette dernière a été suggérée comme outil majeur pour réussir le transfert des ressources publiques du cordon douanier vers la fiscalité domestique et en complémentarité avec les droits d’accises. Nos investigations empiriques soutiennent cette assertion théorique et montrent que le couple TVA-accise joue bien ce rôle de substitut aux recettes de porte en quasi baisse suite au démantèlement tarifaire dans les pays. Néanmoins le rôle d’appui de la TVA et des droits d’accises est limité à partir d’un certain seuil de baisse des recettes de porte, qui traduit aussi le fait que le potentiel de mobilisation fiscale par la TVA dans ces pays est limité et qu’il faudra s’en préoccuper. Dans le second essai nous analysons la transition de seconde génération basée sur les impôts directs (impôts sur les revenus et impôts fonciers). Nous trouvons que les impôts directs sont des outils pauvres de transition fiscale dans les pays en développement. Pourtant, nous trouvons que le développement financier est un médiateur certain et incontestable à une politique de transition fiscale de seconde génération basée sur les impôts directs, car permettant de recouper l’information sur les revenus des contribuables et de générer des traces documentaires à l’administration fiscale, qui permettent d’envisager une mise à fiscalisation des contribuables, gage de recettes fiscales directes supplémentaires dans les pays. Dans le troisième essai, nous nous intéressons à l’effet de la mise en place d’une réforme de transition fiscale sur l’efficience dans la collecte des recettes en menant une étude de cas pour l’union économique et monétaire ouest africaine (UEMOA). Nos résultats supportent l’affirmative, en ce sens que la réforme accroit globalement une mobilisation efficiente des recettes dans la zone UEMOA. Cette efficience entrainerait par ailleurs avec elle une amélioration du climat des affaires dans la zone, suite à la mise en place de cette réforme. Enfin nous terminons cette thèse par un quatrième essai qui interroge quand à lui les impacts distributifs et de pauvreté d’une réforme de transition fiscale basée sur la TVA. Quoique les résultats montrent une incidence régressive de la réforme sur le revenu des ménages, une redistribution par la dépense aurait le mérite d’atténuer l’incidence sociale de cette stratégie de réforme sur le revenu des contribuables.
Keywords: 2SLS-IV model; Accises; Administration fiscale; Analyse des frontières stochastiques; Business climate; Climat des affaires; Computable general equilibrium; Contrôle Synthétique; Coordination fiscale; Corporate tax; Developing countries; Développement financier; Efficience; Efficiency; Effort fiscal; Excise; Exemptions; Exonérations; Financial development; Fiscalité; GMM; Harmonisation; Harmonization; Impôt foncier; Impôt sur le revenu; Impôt sur les sociétés; Income tax; Inequality; Internet; Inégalités; Micro-simulation; Modèle 2SLS-IV; Pauvreté; Pays en développement; Politique fiscale -- Pays en voie de développement; Potentiel fiscal; Poverty; Probit and Logit; Probit et Logit; Propensity scores; Property tax; Réforme fiscale; Scores de Propension; Stochastic frontier analysis; Synthetic control; TVA; Tax administration; Tax coordination; Tax effort; Tax potential; Tax reform; Tax transition; Taxation; Taxes sur le commerce extérieur; Trade taxes; Transition fiscale; VAT; Équilibre général calculable

Adoption des normes IFRS dans l’espace OHADA : Fondement théorique, intérêt et enjeux - Nyasseu, Emma Joachim; Yepdo, Florentin Gaël; Tatang Atabonfack, Pulchérie Léonie; Myskinole, Cheguem Shupo Davine (International Journal of Financial Accountability, Economics, Management, and Auditing, 2021)
Du fait des changements profonds qu’apportent les nouveaux concepts sur lesquels se base le référentiel de l’IASB, le passage aux normes IFRS a été qualifié d’une révolution comptable. Le but d’harmonisation de cette institution se réalise à travers la diffusion mondiale progressive des normes IFRS. Toutefois, les entreprises de la zone OHADA sont concernées par ce changement. Compte tenu de la rareté des travaux de recherche dans le domaine, nous essayons d’analyser à travers ce papier, l’adoption de telles normes en contexte OHADA. Pour y parvenir, cet article rappelle le mécanisme de passage aux normes IFRS dans l’espace OHADA, étudie ensuite l’intérêt pour les entreprises de cette zone et enfin met en évidence les enjeux liés à un tel projet. Les principaux résultats montrent que loin d’être un simple outil de présentation et de communication de l’information financière, les IFRS constituent pour les entreprises de la zone OHADA, un levier d’attraction des investisseurs et d’intégration économique.
Keywords: Normalisation comptable; Normes IFRS; OHADA; Référentiel; Révolution comptable

Firm Performance, Financial Constraints, and Dual-Class Share Structure - Ahamed, Fatematuz Tamanna (Victoria University of Wellington, 2021)
This thesis addresses two aspects of financial constraints focusing, firstly, on the impact of financial constraints on firm performance and, secondly, on the impact of dual-class share structure on financial constraints. The first issue has been addressed in a large number of research studies, but the results are mixed. This study, therefore, conducts a meta-analysis of those earlier studies to provide a summary view of the results which, in contrast to narrative reviews of the empirical literature, provides an objective overview. The second issue examines the impact of dual-class share structures on financial constraints. The period of the global financial crisis is used to test the impact of the state of the economy on that relationship. To examine the impact of financial constraints on firm performance, 26 empirical studies with 189 effect sizes representing listed firms have been analysed. The study finds that overall there is a positive relationship between financial constraints and firm performance. The study also shows that the set of market-based measures of firm performance has a significant negative impact on the relationship, compared with the set of accounting-based measures. In terms of the financial constraints measure, the set of external financial constraints measures have a positive and highly significant impact on the relationship. The meta-regression analysis suggests that the choice of measure, regional difference, journal quality and publication status all have a significant impact on the relationship, and explain the variation in the association. To examine the impact of dual-class share structures on financial constraints the study analyses a sample of non-financial US firms over the period 2002-2018. Share structure is measured by the existence of a dual-class structure and also by excess voting rights and the proximity of the superior class shareholders in such structures. The study also shows that if financial constraints are measured by the WW index, irrespective of how dual-class share structure is measured, it increases the level of financial constraints. Similar results are obtained where financial constraints are measured by the KZ and SA indexes, except where dual-class share structure is measured by the proximity of superior class shareholders. The study also finds that if financial constraints are measured by the WW index, dual-class had a reduced impact during the period of the global financial crisis, thus, providing support for the propping theory. However, if financial constraint is measured by the SA index, dual-class share structure appears to have an increased impact during the GFC years. Among the additional tests, the HM index has been used as a measure of financial constraints, and the findings show that the impact of dual-class structures on financial constraints appears to be driven by their effect on debt constraints. The study also shows that firm age moderates the impact of dual-class share structures if financial constraints are measured by the WW index. The KZ, WW, and SA indexes are based on firm characteristics and, therefore, the study also tests for an impact of dual-class structures when financial constraint is measured by a text-based index, the BLM index. However, the results do not provide evidence of an impact in that case.
Keywords: Dual-class share structure; Financial Accounting; Financial Constraints; Firm Performannce; Meta analysis

Value Relevance of Integrated Reporting using a Novel Approach: Comparative Cross Country Evidence of Mandatory and Voluntary Implementers - Mohaimen, F. J. (Victoria University of Wellington, 2021)
This thesis examines the value relevance of accounting information under integrated reporting (IR) in a comparative mandatory and voluntary setting. A meta review is conducted of all published work focusing on integrated reporting since 2011, which provides detailed insight into the gaps in the IR literature. Multiplicative log-linear model is used in measurement, which is a novel technique that mitigates the shortcomings of traditional value relevance models. The findings show that value relevance of summary accounting information increases after the implementation of IR in the mandatory setting. In the voluntary setting, market effect and the existing reporting paradigm effect the value relevance of accounting information under IR. If the market is large and existing reporting requirements are robust voluntary adoption of IR has minimal to no effect. However, in smaller markets with less rigorous reporting environment, adoption of IR does result in increased value relevance of accounting information. Compared to traditional models, the multiplicative model provides estimates that are more stable over time and shows better explanatory power. Overall, the findings of this thesis show that capital providers value the information content of IR under specific circumstances. This thesis contributes to the IR and value relevance literature by providing the first comparative cross-country evidence of the effect of IR in the change in value relevance of reported accounting information. It provides policy relevant input to the standard setters of IR by demonstrating the effect of IR in the decision usefulness of summary accounting information. The thesis further provides robust evidence of the efficacy of using the multiplicative log-linear model in measuring value relevance instead of the traditional linear additive models.

La publication des informations sociétales suivant les lois comptables revisées OHADA - Guimezap Épse Choukem, Claire (Revue Française d'Economie et de Gestion, 2021)
Dans un contexte marqué par le développement durable, le législateur OHADA n’a eu de cesse d’être accablé de toutes parts pour son statisme vis-à-vis de la montée des problématiques sociétales. Au lendemain des reformes du système comptable OHADA, les problématiques sociétales ont une fois de plus raté le rendez-vous de la normalisation. Toutefois, de nombreuses entreprises continuent à publier leurs informations sociétales parallèlement à leur communication financière. A cet effet, le problème que soulève cet article est celui de la compréhension des modes de production et de diffusion des informations extra-financières en l’absence d’une réglementation en la matière. Une étude empirique de nature descriptive est menée auprès d’un échantillon de 120 entreprises diffusant leurs informations sociétales au sein de l’espace OHADA. Il en ressort que le site internet et l’implication dans le développement de la communauté locale sont apparue respectivement comme support et thème de diffusion les plus utilisés dans l’espace OHADA en matière de reporting sociétal sous la pression de certaines parties prenantes notamment les associations consuméristes, les départements ministériels en charge de l’environnement, du travail et de la sécurité sociale. In a context marked by a widespread awareness of the needs of sustainable development, the OHADA legislator has been constantly burdened on all sides for its statism to the rise of societal problems. However, After the reform of the OHADA system, sustainability problems once more did not met up with the appointment of normalization. However, several enterprises continue to publish their societal information in parallel with their financial communication. As such, the problem raised by this article is that of understanding the mode of production and disclosure of non-financial information in the absence of a regulatory framework. A descriptive empirical analysis is carried out with a sample of 120 enterprises which propagate their societal information in the OHADA zone. It reveals that internet websites and implication in the development of the local community are respectively the medium and theme of the most used disclosures in the OHADA zone with regards to sustainability reporting under the pressure of some stakeholders especially consumer associations, ministerial departments in charge of the environment labor and social security.
Keywords: Accounting law; CSR; Corporate Social Responsibility; Droit comptable; Information sociétale; Parties-prenantes; RSE; Responsabilité Sociétale de l'Entreprise; Stakeholders

Securities regulation, enforcement and market integration in the development of sub-Saharan Africa's capital markets - Aziza, Onoriode Reginald (University of Oxford, 2021)
This thesis examines securities market development in sub-Saharan Africa, focusing on securities law, securities law enforcement and securities markets integration. Adopting a primarily comparative methodology, the thesis examines the continued relevance of securities markets in sub-Saharan Africa; the way selected countries in the region regulate their markets and enforce compliance with securities law; and the potential of market integration to promote market development. This thesis advances 4 main claims. First, empirical evidence supports the link between liquid securities markets and economic growth, independent of the level of banking development. In this sense, securities markets can act as good complements to banks in providing capital to the real economy. Second, at the minimum, there is an arguable preliminary case that rules of securities regulation can hinder market development in select countries in sub-Saharan Africa, by imposing high compliance costs and eligibility requirements, without commensurate benefits in greater liquidity or reduced cost of capital. Third, enforcement of securities regulation in sub-Saharan Africa is generally weak. Whilst public regulators often have formal powers, budgets and staff; actual enforcement activity is sometimes limited by inadequate market monitoring and reliance on criminal as opposed to administrative sanctions. Poor public enforcement, in turn, reinforces poor private enforcement, leading to reduced market participation, illiquidity, and ultimately market underdevelopment. Fourth, although increased market integration can go a long way in facilitating market development in the region, integration cannot be a short/medium term solution to market underdevelopment in sub-Saharan Africa, given the significant economic, political and socio-cultural barriers to integration initiatives in the region. Ultimately, to develop their securities markets, policymakers in sub-Saharan Africa must focus their attention on making and credibly enforcing market-friendly rules of securities regulation. The thesis explores some ways this may be realistically accomplished.
Keywords: Africa; Capital Markets; Capital market; Developing countries; Fintech; Going public (Securities); Market Integration; Securities; Securities Law; Securities Law Enforcement; Sub-Saharan Africa

A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa - Baines, Daniel (University of Pretoria, 2021)
A constitutional analysis of a differentiated tax treatment of residents and non-residents in respect of income deriving from immovable property in South Africa', Daniel Baines explores whether South African resident taxpayers' constitutional rights to equality and property are infringed by current laws which tax residents at higher rates than non-residents on rental income and proceeds from the disposal of fixed property. He aptly sets out what the right to equality and property entails and how these relate to taxpayers. He finds that the higher effective tax rates paid by residents violates their constitutional right to equality. The thesis provides valuable insight into a resident's right to equality and property in terms of current tax rates and illustrates how current tax rates are unconstitutional. The recommendations brought forward contribute toward the discussion of how tax rates should be altered in order to ensure that residents' constitutional rights are no longer violated.
Keywords: Immovable property; Income tax; South Africa; Tax treatment

A comparative analysis between the Turkish Financial Reporting Standard for large and medium-sized entities and the OHADA accounting system - Diallo, Amadou Thierno (Sakarya Üniversitesi, 2021)
The rapidly growing bilateral and multilateral economic relationship between Turkey and African countries leads to the necessity of understanding each other's business and financial environment. Therefore, the accounting system as a fundamental tool for organizing and disseminating financial information should be accessible and understood by business actors and other stakeholders in these areas. Furthermore, the lack of study related to this subject has led us to carry out this comparative analysis between the two accounting systems by comparing financial statements prepared under each one and analyzing their main similarities and differences. The main purpose of this study is to highlight major differences and similarities between the SYSCOHADA and the FRS for LMSE. Also, the study is aimed to get a good understanding of both accounting sets and help practitioners and businessmen, and women operating in these places to have a good knowledge of the accounting regulations related to each country. On a topic basis and based on financial statements prepared following the SYSCOHADA rules and restated to be adapted to the FRS for LMSE, all main differences and similarities were thoroughly analyzed. Following the case study and the thematical analysis of different accounting topics, it can be understood that the two accounting sets differ to some extent due to philosophical approach on some topics such as the prudence principle where the SYSCOHADA, contrary to the FRS for LMSE, does not allow the recognition of potential profit resulting from currency translation gains related to receivable and payables until such profit becomes certain. However, these two sets also share some major similarities due to their proximity in some way to the IAS/IFRS. The effect of the main differences between the two sets can be noticed in the restated financial statements. The annual net income following the FRS for LMSE increased compared to the initial annual net income in the SYSCOHADA. Also, total assets and liabilities restated following the FRS for LMSE have decreased compared to the SYSCOHADA financial statements. Türkiye ile Afrika ülkeleri arasında hızla büyüyen ikili ve çok taraflı ekonomik ilişkiler, birbirlerinin iş ve finans ortamını anlama zorunluluğunu doğurmaktadır. Bu nedenle, finansal bilgilerin düzenlenmesi ve yayılması için temel bir araç olarak muhasebe sistemi, bu alanlardaki iş aktörleri ve diğer paydaşlar tarafından erişilebilir ve anlaşılabilir olmalıdır. Ayrıca bu konuyla ilgili çalışma eksikliği, iki muhasebe sistemi arasında bu karşılaştırmalı analizi, her biri altında hazırlanan finansal tabloları karşılaştırarak ve temel benzerlik ve farklılıklarını analiz ederek yapmaya yöneltmiştir. Bu çalışmanın temel amacı, SYSCOHADA ve BOBİ FRS arasındaki önemli farklılıkları ve benzerlikleri vurgulamaktır. Ayrıca, çalışma hem muhasebe standartları iyi anlamak hem de uygulayıcılara ve bu yerlerde faaliyet gösteren iş adamlarına her bir ülkeyle ilgili muhasebe düzenlemeleri hakkında iyi bilgi sahibi olmalarına yardımcı olmayı amaçlamaktadır. Konu bazında ve SYSCOHADA kurallarına göre hazırlanmış ve BOBİ FRS' ye uyarlanmak üzere yeniden düzenlenen mali tablolara dayalı olarak, tüm temel farklılıklar ve benzerlikler kapsamlı bir şekilde analiz edilmiştir. Vaka çalışması ve farklı muhasebe konularının tematik analizi sonucunda, iki muhasebe setinin bir ölçüde felsefi yaklaşım nedeniyle ihtiyat ilkesi gibi bazı konularda farklılık gösterdiğini anlaşılmaktadır. SYSCOHADA, BOBİ FRS'nin aksine alacak ve borçlara ilişkin kur farkı kazançları kaynaklanan potansiyel kârın kesinleşene kadar muhasebeleştirilmesine izin vermemektedir. Bununla birlikte, bu iki muhasebe seti, UFRS/UMS'ye bir şekilde yakın olmaları nedeniyle bazı önemli benzerlikleri de paylaşmaktadırlar. İki sistemin temel farkların etkisi, yeniden düzenlenen mali tablolarda fark edilebilir. BOBİ FRS'yi takiben yıllık net gelir, SYSCOHADA'daki yıllık net gelire kıyasla artmıştır. Ayrıca, BOBİ FRS'yi takiben yeniden düzenlenen toplam varlıklar ve yükümlülükler, SYSCOHADA finansal tablolarına kıyasla azalmıştır.
Keywords: Accounting standards; Accounting systems; Büyük ve orta boy işletmeler için finansal raporlama standardı; Comparative analysis; Financial reporting standard for large and medium size enterprises; Financial reporting standards; Finansal raporlama standartları; Karşılaştırmalı analiz; Muhasebe sistemleri; Muhasebe standartları; Turkish Financial Reporting Standards; Türkiye Finansal Raporlama Standardı

Transition from Local Accounting Standards to International Accounting Standards: A Comparison Between the OHADA Member Countries and Turkey - Diallo, Amadou Thierno; Çevi̇K, Zülküf (Yorum Yönetim Yöntem Uluslararası Yönetim Ekonomi ve Felsefe Dergisi, 2021)
This study tries to get a clear grasp of the factors that might play positively or negatively in a country’s convergence or adoption of the international financial reporting standards (IFRS). Through a comparative analysis between Turkey and the OHADA countries and based on the existing literature, the transition process towards the IFRS and challenges faced by each one is discussed from a historical perspective to the level of development. As a result, it is understood that the adoption or convergence towards the IFRS can be a challenging and a long-term process requiring multiple adjustments. Also, countries may differ in terms of historical past, level of development, cultural and socio-economic aspects which can all influence their transition. In addition, given the lack of study on the new adoption of the IFRS in the OHADA countries, this paper will contribute to filling the gap in the literature on the transition process. Furthermore, it will help countries which are in their early stage of the transition process to avoid some missteps and learn from others experience to get better prepared for a successful shift towards a fully IFRS compatible accounting system as has done Turkey. Bu çalışma, bir ülkenin uluslararası finansal raporlama standartlarına (IFRS) yakınsaması veya tam olarak benimsemesinde olumlu veya olumsuz rol oynayabilecek faktörleri tespit etmeyi amaçlamaktadır. Türkiye ile OHADA ülkeleri arasında karşılaştırmalı bir analiz yoluyla ve mevcut literatüre dayalı olarak, UFRS'e geçiş süreci ve bu süreçte karşılaşılan zorluklar, tarihsel bir perspektiften tartışılmaktadır. Sonuç olarak, IFRS’in benimsenmesi veya uyumlaştırılmasının zorlu ve birçok ayarlama gerektiren uzun vadeli bir süreç olduğu anlaşılmaktadır. Üstelik bu güçlükler, ülkelerin geçişlerini etkileyebilecek, tarihsel geçmiş, gelişmişlik düzeyi, kültürel ve sosyo-ekonomik yönler açısından farklılık gösterebilir. Buna ek olarak, OHADA ülkelerinde IFRS'in yeni benimsenmesine ilişkin çalışma eksikliği göz önüne alındığında, bu makale geçiş süreciyle ilgili literatürdeki boşluğun doldurulmasına katkıda bulunacaktır. Ayrıca, geçiş sürecinin erken aşamalarında olan ülkelere bazı yanlış adımlardan kaçınmalarına ve diğerlerinin deneyimlerinden öğrenerek, Türkiye'de olduğu gibi tamamen IFRS uyumlu bir muhasebe sistemine başarılı bir geçiş için daha iyi hazırlanmalarına yardımcı olacaktır.
Keywords: Accounting standards; Approche comparée; Comparison; Comptabilité; International Accounting Standards; Local Accounting Standard

Corporate Finance - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book comprises 19 papers published in the Special Issue entitled “Corporate Finance”, focused on capital structure (Kedzior et al., 2020; Ntoung et al., 2020; Vintilă et al., 2019), dividend policy (Dragotă and Delcea, 2019; Pinto and Rastogi, 2019) and open-market share repurchase announcements (Ding et al., 2020), risk management (Chen et al., 2020; Nguyen Thanh, 2019; Štefko et al., 2020), financial reporting (Fossung et al., 2020), corporate brand and innovation (Barros et al., 2020; Błach et al., 2020), and corporate governance (Aluchna and Kuszewski, 2020; Dragotă et al.,2020; Gruszczyński, 2020; Kjærland et al., 2020; Koji et al., 2020; Lukason and Camacho-Miñano, 2020; Rashid Khan et al., 2020). It covers a broad range of companies worldwide (Cameroon, China, Estonia, India, Japan, Norway, Poland, Romania, Slovakia, Spain, United States, Vietnam), as well as various industries (heat supply, high-tech, manufacturing).

Challenges for Responsible Investment in the retirement benefits sector of Kenya - Mathenge, Elizabeth (Victoria University of Wellington, 2021)
Responsible investment (RI) is the investment strategy that incorporates environmental, social and governance (ESG) factors into the investment decision-making process (Hebb, Hawley, Hoepner, Neher, & Wood, 2015). RI has shifted from what was considered a niche market to become one of the fastest-growing areas of finance in many parts of the world (PRI, 2019b). However, a closer look at the development of RI and adoption rates in countries and regions reveals that RI is not commonly practised in sub-Sahara Africa (except for South Africa). This study explores the critical challenges for RI development in the retirement benefits sector of Kenya and, by engaging with a variety of key stakeholders, proposes how to overcome the identified challenges. It contributes to the literature on challenges for RI in a developing country by offering an in-depth case study of the retirement benefits sector.My study employs qualitative methods to collect and analyse data collected from semi-structured interviews with 22 participants (asset managers, regulators and capital market experts, and a council member of the Association of Retirement Benefits Schemes of Kenya) as well as a collection of published documents by government agencies in Kenya. Also, I analysed 10 annual reports to assess the kind of ESG information that is disclosed by listed companies. My study explores, in particular, how actors in the retirement benefits sector conceptualise RI. It identifies the leading ESG factors in Kenya and draws on the business-case approach to RI to explore whether the participants consider those factors as material risk factors that present both risks and opportunities to the investment decision-making process. Further, my study identifies the specific barriers for RI development and proposes how to overcome them. The findings show that participants define RI using several terminologies. This is consistent with the existing literature. My study finds that all participants consider corporate governance as a material risk factor that can impact the financial returns of a portfolio. However, most of the asset managers do not think that the environmental and social factors can present material risk factors to their investment decision-making process. Although over a third of the asset managers recognise that the environmental and social issues in Kenya present business opportunities to retirement benefits schemes, there is a shortage of well-structured assets in those areas. Further, this study identifies five specific barriers for RI development: diversification challenges; a lack of ESG data; a lack of demand/incentives; short-termism; and the demand for high financial returns and a lack of awareness and expert knowledge of RI practices. My study recommends that the National Treasury of Kenya develops RI policy for the entire finance sector. In addition, the findings support a recommendation for the Capital Markets Authority and the Retirement Benefits Authority to embark on capacity building programmes to educate the actors in the finance sector on RI strategies and to create awareness of the impact of ESG on financial returns in the long run.
Keywords: Investment and Risk Management; Kenya; Responsible investment; Retirement benefits schemes

Governance of non-bank systematically important financial institutions - Morbee, Katrien (University of Oxford, 2021)
This thesis identifies the circumstances under which corporate governance regulation can help gain traction to minimise systemic risk. Systemic risk is the risk that local losses spread through the financial system and badly affect the financial system and the real economy. Excessive risk-taking by financial institutions can contribute to such systemic risk. Prudential regulation and supervision of financial institutions leave corporate decision-makers with room for discretion to increase or decrease systemic risk. The incentives of these decision-makers are not necessarily aligned with minimising systemic risk. The thesis shows that this problem exists across different business models. More specifically, it identifies perverse incentives in the case of systemically important banks, CCPs, mutual funds, and hedge funds. The need for corporate governance regulation therefore lies in the inherent incompleteness of prudential regulation and supervision. Corporate governance regulation can help fill this gap by regulating the environment within which choices are made within these types of institutions. The analysis has three steps. First, it characterises the systemic importance of financial-sector activities carried on outside the context of ‘banks’. The governance literature so far has focused on the ‘systemic externalities’ created by banks. However, our analysis shows that other non-bank SIFIs generate similar systemic externalities with socially harmful consequences. These systemic externalities are not considered by SIFIs when taking business decisions. In a second step, the thesis shows that prudential regulation and supervision are incomplete and leave room for governance regulation to fill in the gaps. The final step shows that a corporate governance framework focused solely on the interests of shareholders will have negative consequences for systemic stability. Given such divergence between the decision-makers’ and society’s interests, corporate governance regulation can complement the traditional prudential framework.
Keywords: Asset managers; Central counterparties; Corporate governance; Finance; Non-bank financial institutions; Systemic risk

Regulatory measures to address bank failures in Zimbabwe - Nyaude, Ashley Batsirai (University of Pretoria, 2021)
The main rationale of prudential bank regulation and supervision of banks has traditionally been to ensure the safety and soundness of banks and protection of depositors. However, best practice standards in bank supervision acknowledge that it is impossible to completely prevent bank failures. Therefore, it is crucial to have regulatory measures in place to deal with banks that fail. Banks are core players in the financial system as the intermediaries between savers and users of capital. In addition, banks provide critical services to consumers, small and medium-sized businesses, large corporate entities and governments who rely on them to conduct their daily business, both at domestic and international level. Banks also fulfil a sui generis role that sets them apart from other financial institutions that are role players in the financial system because, inter alia, they hold “highly” liquid liabilities in the form of deposits that are repayable on demand; they extend long-term loans that may be difficult to sell or borrow against on short notice; they are the back-up source of liquidity to all other institutions (financial and non-financial); and, are also the transmission belt for monetary policy. Unlike other players in the financial system, banks are vulnerable to loss of public confidence and to liquidity risk. Liquidity risk being the risk that a bank will not have sufficient cash to meet short term obligations and the fact that a "run on the bank" by depositors can result in devastating liquidity drainage. Because banks play a special role in the economy and their failure may have a significant impact on financial stability, they need a special approach when they become insolvent or are likely to become insolvent. The 2008 Global Financial Crisis (“GFC”) demonstrated the importance of special resolution regimes for banks; and the need to balance the interests of shareholders, creditors and depositors, while promoting financial stability objectives. Given the critical role of banks in the economy the need is clear for a special resolution regime for banks that provides a legal framework for regulators that avails to them a suite of resolution tools which they can apply to resolve the bank in an orderly manner; to rescue those parts of the bank that may still be viable and to liquidate those parts that are not whilst avoiding a drain on public funds. In order to deal with bank failures in Zimbabwe, the Banking Act [Chapter 24:20] has provided for the mechanism of curatorship since 2000, as a rescue measure aimed at restoring failing banks to economic viability. Curatorship has over the years been applied with mixed success; consequently, Zimbabwe has undertaken a number of reforms which include the enactment of the Troubled Financial Institutions (Resolution) Act in 2005; and the introduction of the problem bank regime via the Banking Amendment Act of 2015. Throughout these reforms, Zimbabwe has elected to retain curatorship, which was once a standalone process in banking legislation to enable bank rescue; and assimilated it into a broader bank resolution framework. This study seeks to determine whether Zimbabwe’s resolution regime requires to be strengthened and if so, to recommend reforms that will align the resolution regime in Zimbabwe with international best practice. For such purpose it will draw upon the Financial Stability Board’s Key Attributes of Effective Resolution Regime as international best practice benchmark. It will further also consider guidance yielded by a comparative study of the resolution regimes in the United Kingdom and South Africa.
Keywords: Bank failure; Bank supervision; Zimbabwe

Allocating rights between nations: Legitimacy and justice in international tax policy - Ozawa Ozai, Ivan (McGill University, 2021)
Although extreme poverty has decreased in the last decades, we are a long way from eradicating global poverty. Similarly, the world has seen a considerable decrease in global inequality due to recent developments in emerging economies, but overall inequality between nations has risen in the last decades. International tax law may have a relevant role in improving or worsening global inequality. Extensive research has shown that the present international tax system was designed in a way that tends to benefit high-income economies. However, there has been no significant discussion about whether and how international tax law rules should be changed to address global inequality. The main goal of this thesis is to analyze the existing legitimacy and distributive justice issues that limit the ability of lower-income countries to raise tax revenues and consider what can be done to make the current international tax regime more aligned with global justice principles.The thesis builds on the contemporary literature in international political economy and global distributive justice and puts forth a normative framework for allocating the international tax base among states. First, it analyzes some of the legitimacy deficits of the present international tax system. In contrast to prevailing views about improving legitimacy, it demonstrates the shortcomings of focusing solely on making international tax policymaking processes more inclusive and argues for a greater focus on global distributive justice. It then analyzes the main tax theories that have defined international tax relations to date and demonstrates some of their limitations. The final part of the thesis puts forth normative principles that integrate distributive justice and considers the practical implications of the proposed normative framework for some of the most recent issues discussed in international tax policy
Keywords: International tax; International tax policy